Pemanfaatan API RajaOngkir untuk Cek Ongkos Kirim Otomatis pada Pembangunan Website E-Commerce menggunakan Framework Codeigniter (Studi Kasus: Jingga Hijab) - Kevin Aditya Firmansyah Putra; Issa Arwani; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Jingga is a local hijab brand that currently serves retail purchases. Previously, Jingga only served wholesale purchases. The promotion process is carried out through social media, while the transaction process is carried out via WhatsApp. Because previously it only served wholesalers, this manual transaction process was still sufficient because there were not as many wholesale buyers as retail buyers. However, because currently Jingga also serves retail purchases, the transaction process like this is certainly less efficient because there are definitely more retail buyers than wholesale buyers. To facilitate this, an e-commerce website was built using the waterfall method complete with management systems such as product management, transactions and shipping. In addition, integration was also carried out with RajaOngkir, a service provider of information regarding freight forwarding and shipping costs, for an automatic shipping cost calculation system. The website is tested using black box testing and compatibility testing. From the test results, it was found that the website can be run well and in harmony with system requirements, and the website can be run in various types of browsers.